Objectives of Islamic Marriage: A Study of the Primary and Subsidiary Objectives: مقاصد الزواج الشرعية ـ دراسةٌ لأهم مقاصد الزواج الأصلية والتبعية - Firano, Ismail (Dirasah International Journal of Islamic Studies, 2024)
Holy Qur’an, Hadith, Ijma, Qiyas, and Ijtihad. Islamic banking has rapidly been growing in the modern economic world as an alternative to conventional banking. It is expected that Islamic banking operations will not only comply with the Shari’ah but also contribute towards achieving the Maqasid-al-Shari’ah (objectives of Shari’ah), which is the ultimate welfare of the Muslim Ummah and the human being. The findings of several studies showed that Shari’ah compliance is the single most important factor for choosing Islamic banking. Unfortunately, many recent studies revealed that many Islamic banks are violating their obligation of Shari’ah compliance. Hence, the paper aims at understanding the Shari’ah foundation of Islamic banking to examine that the modes of Islamic banking are based on the principles of Shari’ah. It also incorporates the major components of Shari’ah and its concept of economic tools such as ownership, wealth, money, capital, trust, and accountability to have a comprehensive idea about the Shari’ah foundation of Islamic banking. The methodology used in this conceptual study is a critical analysis of the literature survey. The literature on the concept of Shari’ah basis of Islamic banking is read to understand the basic components of Shari’ah and its principles to govern economic practices to examine its application in the Islamic banking industry and identify the Shari’ah foundation of the modes and contracts used by the modern Islamic banking industry.